GROWTH AND YIELD OF PEANUT AS AFFECT BY PLANTING METHOD AND PLANT POPULATION - & Al-Muger, AL-Hilfy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
A field experiment was conducted at the experimental field, Dept. of Field Crop , Coll. of Agric. Univ. of Baghdad during the yeans of 2010 and 2011 to study growth and yield of peanut as affected by planting methods and plant population. A factorial arrangement in RCBD design with four replications were used , with two factors, the first one: three planting methods (planting on East, West and Twin rows) and the second factor: four spacing between plants (15, 25, 35 and 45) cm. The results showed that the planting method on east produced highest dry weight (117.51, 100.64) g.plant-1, growth rate (625.10, 532.40) mg.plant-1.day-1 , seed yield per plant (25.16, 32.25)g.plant-1, protein percent (26.01, 26.20)% for both seasons respectively. Moreover planting method on twin row gave highest pod yield (4180, 3842) kg. ha-1, oil percentage (46.00, 46.20)% for both seasons respectively. The highest plant density 15 cm between plants gave highest pods yield (3960 3031 kg.ha-1, seed yield (2328.7, 1761.0) kg. ha-1, oil percentage (46.50, 46.28)% for both seasons, respectively. The lowest plant density 45 cm between plants gave highest dry weight (124.07, 114.07) g.plant-1, growth rate (659.90, 603.50) mg. plant-1.day-1, seed yield per plant (36.05, 31.07)g. plant-1, protein percentage (26.40, 26.20)% for both seasons, respectively. The planting method on twin row with the high plant density 15 cm gave highest seed yield (2894.1, 2542.0) kg.ha-1, while the planting method on west and the low plant density 45 cm gave the lowest seeds yield (1051.3, 912.0) kg.ha-1 for both seasons, respectively.